Valuing the non-market benefits of estuarine ecosystem services in a river basin context: Testing sensitivity to scope and scale. (5th February 2016) - Pinto, R.; Brouwer, R.; Patrício, J.; Abreu, P.; Marta-Pedroso, C.; Baeta, A.; Franco, J.N.; Domingos, T.; Marques, J.C.
Abstract: A large scale contingent valuation survey is conducted among residents in one of the largest river basins in Portugal to estimate the non-market benefits of the ecosystem services associated with implementation of the European Water Framework Directive (WFD). Statistical tests of public willingness to pay's sensitivity to scope and scale are carried out. Decreasing marginal willingness to pay (WTP) is found when asking respondents to value two water quality improvement scenarios (within sample comparison), from current moderate water quality conditions to good and subsequently excellent ecological status. However, insensitivity to scale is found when asking half of the respondents to value water quality improvements in the estuary only and the other half in the whole basin (between sample comparison). Although respondents living outside the river basin value water quality improvements significantly less than respondents inside the basin, no spatial heterogeneity can be detected within the basin between upstream and downstream residents. This finding has important implications for spatial aggregation procedures across the population of beneficiaries living in the river basin to estimate its total economic value based on public WTP for the implementation of the WFD. Graphical abstract: Highlights: The non-market benefits of WFD implementation are valued in one of the largest river basins in Portugal. Tests are carried out for sensitivity to scope and scale. Public WTP for incremental water quality improvements declines once GES is achieved. Respondents living outside the river basin value water quality improvements significantly less than respondents living inside the basin. No spatial heterogeneity is found inside the river basin and public WTP for the Mondego estuary and river basin is the same.